A Summary of N, P, and K Research with Cucumber in Florida - George Hochmuth; Ed Hanlon (EDIS)
Revised! SL 335, a 15-page fact sheet by George Hochmuth and Ed Hanlon, summarizes the historical Florida research literature on nitrogen, phosphorus, and potassium fertilization of cucumber. Includes references. Published by the UF Department of Soil and Water Science, October 2010.